The Evaluation of Forest Cultural Value Based on WTP: A Case Study in Diebu County of Gansu Province in China - Zhang, Ying; Zhou, Xiaohong (Journal of Environmental Accounting and Management, 2026)
Cultural value is regarded as an important component of forest ecosystem services, which has been received great attention to a certain extent for the relevant research in recent years. In this study, taking Diebu County of Gansu Province in China as an example, the impact factors of Willingness to Pay (WTP) of forest cultural value is analyzed by adopting Logistic Regression Model (LRM) and Contingent Valuation Method (CVM), and the value of forest culture in Diebu County is estimated. The result shows that WTP of forest cultural value in Diebu County is rather low, the percentage of people who are willing to pay only accounts for 35.29% of total survey population. Impact factors ofWTP for cultural value mainly contain the education level, professional knowledge, personal income and so on, among which the impact of educational level for WTP is least, and the personal annual income is largest. In addition, the personal annual income is also the most prominent impact factor for not willing to pay for forest cultural value. Mean WTP per capita for forest cultural value of Diebu County is at the range between 18.96 RMB/a and 53.81 RMB/a. The results are calculated according to the population and number of the travelers in 2016. With the evaluation, forest cultural value of Diebu County is about between 8.2741 million RMB and 23.4390 million RMB in that year. The discussion is also raised according to relevant results in the research.